PEMBERDAYAAN BERBASIS MASJID : BENTUK AKTUALISASI PEMBERDAYAAN DI MASJID NURUL HIKMAH KEMANTAN AGUNG, KERINCI-JAMBI - Yulia - Annisa; Darusman Darusman (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2022)
This article wants to examine the actualization of mosque-based empowerment activities as a transformation of the main function of the mosque into a center for community empowerment activities around the mosque. This is due to the lack of function of the mosque optimally by the local community because it is far from the resident environment. In the end, the management carried out a transformation by improving mosque institutions by optimizing the potential possessed by the community through mosque facilities in order to achieve a better life for the community around the mosque. The research method used is descriptive qualitative data collection through interview scripts, field notes, and other documentation. This study found that the forms of empowerment activities at the Nurul Hikmah mosque were actualized in the fields of religion, education and community service, economics, health (free treatment for the elderly), environmental conservation (toga gardens) and partnerships.